Melatonin administration provokes the activity of dendritic reticular cells in the seminal vesicle of Soay ram during the non-breeding season - Hanan H. Abd-Elhafeez (Nature Portfolio, 2021)
Abstract Dendritic cells (DCs) are innate immune cells which engulf, process and present antigens to the naïve T-lymphocyte cells. However, little is known about the effect of melatonin on the DCs. The present study aimed to investigate the morphology and distribution of the DCs by transmission electron microscopy and Immunohistochemistry after melatonin administration. A total of 8 out of 15 adult ram was randomly selected to receive the melatonin implant and the remaining 7 animals received melatonin free implants. DCs showed positive immunoreactivity for CD117, S-100 protein and CD34. There is an obvious increase in the number of the positive immunoreactive cells to CD3, estrogen receptor alpha and progesterone in the treated groups. The expression of CD56 and MHCII in the DCs was abundant in the treated groups. The ultrastructure study revealed that melatonin exerts a stimulatory effect on the DCs which was associated with increment in the secretory activity of DCs. The secretory activity demarcated by an obvious increase in the number of mitochondria, cisternae of rER and a well-developed Golgi apparatus. The endosomal- lysosomal system was more developed in the treated groups. A rod-shaped Birbeck granule was demonstrated in the cytoplasm of the melatonin treated group. DCs were observed in a close contact to telocytes, T-Lymphocytes, nerve fibers and blood vessels. Taken together, melatonin administration elicits a stimulatory action on the DCs and macrophages through increasing the size, the number and the endosomal compartments which may correlate to increased immunity.